Head loss in laser-perforated thin-walled polyethylene pipes for irrigation - Verônica G. M. L. de Melo; José A. Frizzone; Antonio P. de Camargo; Wagner W. Á. Bombardelli (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT For reducing fixed and operational costs in pressurized irrigation systems, thin-walled polyethylene pipes with laser-perforated orifices are manufactured to operate under low pressure (up to 100 kPa). Hydraulic characterization of these materials is essential for designing irrigation systems. Considering the material elasticity and the thin wall thickness (about 200 μm), the internal diameter of these pipes may vary according to the operating pressure, resulting in changes of head losses. The purpose of this study was to analyze the head loss in flexible pipes with laser-perforated orifices, and to estimate the maximum length of laterals based on criteria of water distribution uniformity. Non-perforated pipe samples were tested to obtain equations of friction loss. Equations were fitted as a function of flow rate and pressure head at the pipe inlet, and, alternatively, the Darcy-Weisbach equation was modified considering the diameter expressed as a power-law function of pressure head. The equation of head loss as a function of flow rate and pressure head provided proper estimations and considered effects related to changes in the diameter of plastic pipes due to variations in the pressure head. The Darcy-Weisbach equation can be employed for estimating head loss in flexible pipes, whose diameter varies due to pressure, but the diameter must be calculated as a function of the pressure head at the lateral inlet.